1994
DOI: 10.1115/1.2902133
|View full text |Cite
|
Sign up to set email alerts
|

A Knowledge-Based Diagnostic Approach for the Launch of the Auto-Body Assembly Process

Abstract: This paper is the first attempt to implement a knowledge-based diagnostic approach for the auto-body assembly process launch. This approach enables quick detection and localization of assembly process faults based on in-line dimensional measurements. The proposed approach includes an auto-body assembly knowledge representation and a diagnostic reasoning mechanism. The knowledge representation is comprised of the product, tooling, process, and measurement representations in the form of hierarchical groups. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(44 citation statements)
references
References 8 publications
(8 reference statements)
0
43
0
1
Order By: Relevance
“…Since the design task function is an implicit function, the partial derivatives are resolved as in Eq. (6), where ''f T,k,i '' (f T,k,t ) represents the partial derivative of the design function task ''f T,k '' with respect to the ith (tth) design parameter. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the design task function is an implicit function, the partial derivatives are resolved as in Eq. (6), where ''f T,k,i '' (f T,k,t ) represents the partial derivative of the design function task ''f T,k '' with respect to the ith (tth) design parameter. …”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that only 60-70% of Right First Time (RFT) is reached during the design stage [5,6]. Failures that are not predicted during the design phase can appear during ramp-up, which in turn, require engineering changes thus, leading not only to significant cost increase but also trigger delays in the launch of a new product.…”
Section: Introductionmentioning
confidence: 99%
“…The methodologies developed so far are based on measuring the parameters throughout the process and analyzing them for detecting the process deviations and identifying the root causes of the process anomalies. Such methods can be divided into two groups: (1) methods established based on the modeling of process variation propagation [10][11][12], and (2) methods based on Statistical Process Control (SPC) [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…China E-mail: huawang@sjtu.edu.cn Tel: +86- (OCMM) have recently become popular. Much research [2, 4,7,8] on OCMM data processing has been conducted. Some main topics of the research are the knowledge-based diagnostic approach [3], correlation and principal component analysis [5,6], time series theory [8,10], characteristic detection using wavelets [12], fixture failure modeling [9,13] and stream-ofvariation theory [11].…”
Section: Introductionmentioning
confidence: 99%